2019
DOI: 10.1103/physreva.99.032313
|View full text |Cite
|
Sign up to set email alerts
|

Light-cone and local front dynamics of a single-particle extended quantum walk

Abstract: We study the light-cone and front dynamics of a single particle continuous time extended quantum walk on a one dimensional lattice with finite range hopping. We show that, in general, for an initially localized state, propagating wave fronts can be characterized as ordinary or extremal fronts with the latter exhibiting an anomalous sub-diffusive scaling behaviour in the front region. We investigate the dynamical global and local scaling properties of the cumulative probability distribution function for the ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…We have comprehensively explored an extension of the EQW, a non-Markovian quantum walk process where the jump sites are selected from a uniform distribution giving rise to hyperballistic diffusion. Even though jumps in QWs have been introduced either in discrete-time 34–40 and continuous-time 4145 models, we highlight that none of these previous works have found the richness of dynamical transitions we have presented herein with our new time-dependent protocol of jumps and two types of coin operators. Our flexible distribution, the q -exponential, allows us to recover both the standard QW in the limit q → 1/2 and the previous proposal q → ∞ 28 , providing a more general framework.…”
Section: Discussionmentioning
confidence: 90%
“…We have comprehensively explored an extension of the EQW, a non-Markovian quantum walk process where the jump sites are selected from a uniform distribution giving rise to hyperballistic diffusion. Even though jumps in QWs have been introduced either in discrete-time 34–40 and continuous-time 4145 models, we highlight that none of these previous works have found the richness of dynamical transitions we have presented herein with our new time-dependent protocol of jumps and two types of coin operators. Our flexible distribution, the q -exponential, allows us to recover both the standard QW in the limit q → 1/2 and the previous proposal q → ∞ 28 , providing a more general framework.…”
Section: Discussionmentioning
confidence: 90%
“…In a walk with nearest and next nearest hopping, we showed that there is a transition from a regime with one causal cone to a regime with two nested causal cones. Further, we showed that the local probability densities exhibit anomalous subdiffusive scaling near extremal fronts and the nature of the scaling depends on the order of the front [20]. We also connected the study to that of spin-chains where the existence of such upper bounds on the spread or Lieb-Robinson (LR) bounds for the speed with which information propagates has been earlier studied [24][25][26].…”
Section: Introductionmentioning
confidence: 80%
“…They have been shown to exhibit ballistic propagation instead of the diffusive behaviour expected of a classical random walk [18][19][20][21][22][23]. In recent work [20], we showed that interesting 'causal light cone structures' appear in a single particle continuous time quantum walk with a finite range of hopping. In the bulk, the walk exhibits ballistic propagation of wave fronts.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations